2012
DOI: 10.1111/j.1442-9071.2012.02798.x
|View full text |Cite
|
Sign up to set email alerts
|

Bleb vascularity following post‐trabeculectomy subconjunctival bevacizumab: a pilot study

Abstract: Background: To determine whether postoperative subconjunctival bevacizumab significantly alters bleb vascularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…The beneficial effect of bevacizumab was confirmed in more recent studies, which showed that intraoperative subconjunctival bevacizumab administration was safe and effective in terms of IOP control, although its effect was less prominent than that of MMC (Nilforushan et al, 2012;Sengupta et al, 2012). On the other hand, several other pilot studies showed that bevacizumab did not affect IOP differently compared to placebo (Sedghipour et al, 2011) or 5-FU (Chua et al, 2012;Jurkowska-Dudzinska et al, 2012;Suh and Kee, 2013). Importantly, all the mentioned studies included a limited number of patients and/or had a short follow-up period.…”
Section: Inhibition Of Vascular Endothelial Growth Factormentioning
confidence: 71%
“…The beneficial effect of bevacizumab was confirmed in more recent studies, which showed that intraoperative subconjunctival bevacizumab administration was safe and effective in terms of IOP control, although its effect was less prominent than that of MMC (Nilforushan et al, 2012;Sengupta et al, 2012). On the other hand, several other pilot studies showed that bevacizumab did not affect IOP differently compared to placebo (Sedghipour et al, 2011) or 5-FU (Chua et al, 2012;Jurkowska-Dudzinska et al, 2012;Suh and Kee, 2013). Importantly, all the mentioned studies included a limited number of patients and/or had a short follow-up period.…”
Section: Inhibition Of Vascular Endothelial Growth Factormentioning
confidence: 71%
“…Bleb vascularity following post-trabeculectomy subconjunctival bevacizumab was assessed in another study by Chua et al and an increasing trend for central bleb avascularity was observed though not statistically significant. 23 However, an increase trend for vascularity in subconjunctival bevacizumab has been observed in earlier studies by Sengupta 16,17 No significant difference in bleb morphological features including vascularity was found between subconjunctival bevacizumab and MMC in earlier studies by Sengupta et al and Niloforushan et al 17,18 Adding single subconjunctival bevacizumab in trabeculectomy with MMC significantly reduced vascularity scores (using IBAS) at one month which disappeared on subsequent follow-up in a study by Kiddee et al 23 We also assessed the histological features of bleb in both groups. The number of fibroblasts was reduced in both groups.…”
Section: Current Eye Researchmentioning
confidence: 97%
“…On the other hand, four further pilot studies showed that administration of bevacizumab (0.2 and 1.25 mg) during trabeculectomy did not affect IOP differently from placebo71 or 5-fluorouracil (5 and 7.5 mg) 7274. Notably, all these studies included small numbers of patients or had a short follow-up duration, meaning that they lacked the necessary power to draw firm conclusions.…”
Section: State Of the Art In Modulation Of Wound Healingmentioning
confidence: 99%